2021
DOI: 10.1109/access.2021.3136026
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Numbering and Condition Recognition on Dental Panoramic Radiograph Images Using CNNs

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In Table 1 , we present the different image analysis tasks on PAN. Seventeen studies reported on detection tasks—where bounding-box-based annotations were performed within an image; 8 , 9 , 15–17 , 19 , 21 , 26 , 27 , 33 , 35 , 39 , 40 , 42 , 43 , 46 , 48 26 studies focused on classification tasks, indicating studies that assigned a label to the entire image—either binary or multi-class; 7–13 , 17 , 20 , 22 , 24 , 25 , 28 , 32 , 34 , 36–38 , 40–45 , 47 , 48 3 studies conducted identification tasks, also bounding-box-based discrimination of object, but among other objects within the same class (e.g. facial recognition).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 1 , we present the different image analysis tasks on PAN. Seventeen studies reported on detection tasks—where bounding-box-based annotations were performed within an image; 8 , 9 , 15–17 , 19 , 21 , 26 , 27 , 33 , 35 , 39 , 40 , 42 , 43 , 46 , 48 26 studies focused on classification tasks, indicating studies that assigned a label to the entire image—either binary or multi-class; 7–13 , 17 , 20 , 22 , 24 , 25 , 28 , 32 , 34 , 36–38 , 40–45 , 47 , 48 3 studies conducted identification tasks, also bounding-box-based discrimination of object, but among other objects within the same class (e.g. facial recognition).…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies, 14 used multi-stage architectures combining different tasks in a pipeline to produce an output. 8 , 9 , 11 , 13 , 17 , 26–28 , 36 , 39 , 40 , 42 , 43 , 48 In contrast, 27 studies used a single model to carry out distinct tasks. 7 , 10 , 12 , 14–16 , 19–25 , 29–35 , 37 , 38 , 41 , 44–47 …”
Section: Resultsmentioning
confidence: 99%
“…Together with data pre-processing and augmentation techniques, Szu-Yin Lin and Hao-Yun Chang have created an innovative and effective two-phase DPR detection and methodology to help dentists in diagnosis by using advanced DL algorithms. Orthodontics, dental restoration, endodontic therapy, implant, impaction, and dental prosthesis are among the dental problems that are instantly detected [ 84 ]. To categorize the teeth positions by using a proposed correlation module that makes use of the information between teeth positions, Zhang et al [ 85 ] employed DL methods and used a particular label creation methodology to partition the teeth classification job before using a multi-task CNN.…”
Section: Resultsmentioning
confidence: 99%
“…Different types of images were used by different researchers based on the techniques they used in DI. Radiographic images [ 16 , 41 , 43 , 56 , 63 , 64 , 65 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 87 , 157 ], near-infrared light transillumination (NILT) [ 88 , 89 , 90 ], intraoral images [ 66 , 86 , 91 , 92 , 93 , 95 , 96 , 97 , 158 , 159 , 160 ], 3D model [ 102 , 113 , 114 , 115 , 161 ] were used in the research for dental diseases diagnostic on the 3D dental model. The studies on the dental disease’s diagnostic on the CBCT dental model used the CT images [ 124 ], 3D CT scans […”
Section: Resultsmentioning
confidence: 99%
“…Factors such as fatigue, emotions and inexperience can contribute to misdiagnosis [9], which impairs the quality of dental treatment [10].…”
Section: Introductionmentioning
confidence: 99%